An Extraordinary Journey: The Memoirs of a Physical Medium by Stewart Alexander - Weaver, Zofia (Journal of Scientific Exploration, 2021)
This is a revised and updated version of Alexander’s book published in 2010 under the same title. The changes are minor; there are some additional reflections on the subject of Spiritualism by the author, but mainly they consist of additional accounts from sitters who have taken part in séances with Alexander since the original publication. Some appear in additional chapters described as “seminars,” reported chronologically, but in fact they are also witness accounts of séance experiences. The most significant addition, in terms of reporting startling new phenomena, is the Epilogue provided by American journalist and author Leslie Kean. There is no index. I found this book very readable. Also, having read it, I would find it difficult to disagree with the descriptions of Alexander by the late David Fontana (who provided the Foreword) and Annette Childs (who provided An Appreciation) as a person of integrity and dedication, as well as intelligence and good humour; in fact, “a true gentleman” (p.xxiii).